IMPLEMENTASI PERATURAN WALIKOTA MEDAN TENTANG ADAPTASI KEBIASAAN BARU PADA COVID-19 DI PT. BISA GROUP PARADISE DYNASTY - Oktavianus The Memori Hondro; Samsul Bahri Pane (STKIP PGRI TULUNGAGUNG, 2022)
The COVID-19 pandemic has greatly impacted all people in various walks of life and sectors of life, especially in the food and beverage service business industry such as at PT. Bisa Group Outlet Paradise Dynasty. So the main step from the government, especially in the city of Medan, is to issue Medan Mayor Regulation No. The method used in this study is a qualitative descriptive method which was conducted by means of open and in-depth interviews. The theory used in this study is the theory of G. Shabbir Cheema and Dennis A. Rondinelli models to determine the success of the implementation of several variables used, namely: environmental conditions, resources, organizational relationships, and characteristics of the implementor. The results of this study based on the presentation and analysis of data by the author, it can be concluded that the implementation of the adaptation of new habits in the conditions of the covid-19 pandemic at the determining paradise dynasty outlet was successfully implemented based on indicators of environmental conditions, resources, organizational relations, and characteristics of the implementor. . However, from the successful implementation of the adaptation, the obstacle encountered was the lack of awareness of visitors to comply with health protocols